2002
DOI: 10.1172/jci0216391
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and mechanisms of macrophage cholesterol efflux

Abstract: The accumulation of cholesterol in macrophage foam cells results from the uptake of retained and modified apoB lipoproteins (1) and is a central event in atherogenesis. Although it has long been known that HDL and its apolipoproteins can stimulate cholesterol efflux from macrophage foam cells (2, 3) and reduce atherogenesis in animal models (4, 5), this area of research has been enlivened by the elucidation of the genetic defect in Tangier disease, a condition in which there is a defect in apolipoprotein-media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
67
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(77 citation statements)
references
References 50 publications
8
67
0
2
Order By: Relevance
“…ABCA1 is highly expressed in the liver and tissue macrophages (32, 33). When mutated, it can cause Tangier disease, which involves abnormally low levels of HDL and premature atherosclerosis (6, 17, 18, 3437). Moreover, myeloid-specific deletion of ABCA1 markedly increased atherosclerosis in mice without affecting plasma lipoprotein levels (6).…”
Section: One Key Cardioprotective Property Of Hdl Involves Reversementioning
confidence: 99%
See 1 more Smart Citation
“…ABCA1 is highly expressed in the liver and tissue macrophages (32, 33). When mutated, it can cause Tangier disease, which involves abnormally low levels of HDL and premature atherosclerosis (6, 17, 18, 3437). Moreover, myeloid-specific deletion of ABCA1 markedly increased atherosclerosis in mice without affecting plasma lipoprotein levels (6).…”
Section: One Key Cardioprotective Property Of Hdl Involves Reversementioning
confidence: 99%
“…In the artery wall, membrane-associated ABCA1 interacts with lipid-free or poorly-lipidated apoA-I to remove excess cholesterol from resident macrophages (17, 18, 77, 78). ApoA-I contains amphipathic α-helices, a structural motif that promotes lipid association (22, 24, 79, 80).…”
Section: Myeloperoxidase (Mpo) a Heme Enzyme That Produces Reactimentioning
confidence: 99%
“…In addition, the nuclear receptor LXR α (liver X receptor α ), which enhances expression of ABCA1 (ATP-binding cassette transporter A1), a protein which mediates cellular cholesterol efflux [102], has also been shown to be a PPAR γ target gene in human and mouse macrophages [103, 104]. Taken together, these data suggest a broader spectrum of PPAR γ effects within the macrophage with the overall balance favouring cholesterol efflux and an antiatherogenic effect.…”
Section: Pparγ-a Key Therapeutic Target In the Human Metabolic Synmentioning
confidence: 99%
“…ABCA1 is a 12-transmembrane protein with ATP binding sites (Walker motifs) located in a large cytoplasmic central region (amino acids 899 – 1120 marked here as D1) and C-terminal cytoplasmic domain (amino acids 1908 – 2261, marked here as D2) [8]. Our studies demonstrated that Nef binds to ABCA1 [1], and identified an DDDHLK motif in the C-terminal cytoplasmic domain of ABCA1 as essential for the Nef interaction with ABCA1 [9].…”
Section: Introductionmentioning
confidence: 99%